2015
DOI: 10.3390/molecules200611604
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Korean Red Ginseng against Alcohol-Induced Fatty Liver in Rats

Abstract: The present study tested the hypothesis that Korean red ginseng (KRG) provides a protective effect against alcoholic fatty liver. Male Sprague-Dawley rats were divided into four groups and fed a modified Lieber-DeCarli diet containing 5% (w/v) alcohol or an isocaloric amount of dextrin-maltose for the controls for 6 weeks: normal control (CON), alcohol control (ET), and ET treated with 125 or 250 mg/kg body weight/day of KRG (RGL or RGH, respectively). Compared with the CON group, the ET group exhibited a sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…Many studies have evaluated the potential beneficial effects of KRG on alcoholic liver disease [11] , [18] , [20] , [21] , [22] . In a preclinical study involving rats [22] , KRG extract’s effect on liver damage induced by short-term and long-term alcohol treatment was evaluated.…”
Section: Alcoholic Liver Diseasementioning
confidence: 99%
See 2 more Smart Citations
“…Many studies have evaluated the potential beneficial effects of KRG on alcoholic liver disease [11] , [18] , [20] , [21] , [22] . In a preclinical study involving rats [22] , KRG extract’s effect on liver damage induced by short-term and long-term alcohol treatment was evaluated.…”
Section: Alcoholic Liver Diseasementioning
confidence: 99%
“…KRG has also been associated with several beneficial effects on liver function and liver disease. First, it has been shown to have a hepatoprotective effect against acute and chronic liver injury caused by a variety of hepatotoxins, which may include hydrogen peroxide [19] , alcohol [11] , [18] , [20] , [21] , [22] , carbon tetrachloride [23] , aflatoxin B1 [24] , [25] , diethylnitrosamine [26] , and viruses [13] , [27] . Second, KRG is associated with antiinflammatory and antioxidative effects in the context of NAFLD [10] , [28] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rats were used as an animal model as its anatomy has a much resemblance with human anatomy 16 .A similar study was done in Korea in 2015, the only difference, they use black Korean ginseng instead of red Korean ginseng they also obtained the same finding 17 . The same species were also used by many workers and they suggested red ginseng may have the potential to ameliorate alcoholic fatty liver by suppressing inappropriate lysis of adipose tissue and preventing unnecessary de novo lipogenesis in the liver, which is mediated by AMPK signaling pathways 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Korean scientists are devoted to the research of Korean red ginseng (KRG) and found the crude extract of KRG acts as an antioxidant and protector in Hepatitis B-induced LF [ 36 ]. Apart from internal etiologies, KRG efficaciously mitigates inflammatory responses against acute LF which caused by physical factors such as Gamma irradiation or chemical factors such as CCl 4 and alcohol [ 37 39 ].…”
Section: Effects Of Ginseng Extract and Formulas On Ofdmentioning
confidence: 99%